Residual stress determination of friction stir welding of 1060 aluminum alloy using X-ray diffraction - Lê Chí Cương; Nguyễn Đức Thành (Journal of Technical Education Science, 2012)
The residual stress distribution in friction stir welding of aluminum alloy 1060 was investigated by using X-ray diffraction. The heat-affected zone had linear sin2 diagram, showing that the crystal is isotropic having small size, which agreed to the microstructure using SEM. Therefore the stress measurement can be carried out without using the oscillated- method. The heat-affected zone had smaller stress value in comparison to other area. In general, the residual stress of friction stir welding give small stress value in comparison to traditional welding methods.